A unique business model for microfinance institution: the case of Assadaqaat Community Finance (ACF) - Huda Mohammad Hagawe; Asma Mobarek; Akmal Hanuk; Ahmad Jamal (Cogent Business & Management)
While access to finance is a key link between economic opportunity and economic outcome, it remains a major barrier for aspiring entrepreneurs. The current research aims to conduct an in-depth case study of Assadaqaat Community Finance (ACF), a unique UK-based community finance institution with the objectives of addressing the global challenges of financial exclusion and social and economic inequalities through entrepreneurship and self-employment. ACF offers free professional training using an innovative and ground-breaking financial model based on Islamic financial principles via the ACF Cycle of Shared Prosperity framework. Semi-structured interviews were conducted with 20 participants including beneficiaries, benefactors and founders to explore the impact of ACF training, advice and mentoring and access to interest-free and debt-free finance in helping participants overcome the challenges and develop feasible business plans for their micro, small and medium enterprises. The results suggest that the beneficiaries are happy and become financially independent within 3–6 months, resulting in the transformation of beneficiaries into benefactors as they are able to contribute back to ACF. We highlight the transformational nature of this unique institutional business model and its applicability for existing Islamic MFIs, allowing them to make a clear contribution to development of sustainable communities. We also argue that the ACF financial model offers a sustainable solution to overcome global challenges and contribute towards achieving the Sustainable Development Goals.